Effect of Laser Intensity on Porous Silicon Morphology - Saleh, Aisha Mahdi Muhammad; Madli, Ali Dakhil; yousif, Amaleed yagoob; Muhammad, Ali Latif Murtadha; Jassim, Mohsen Abdullah; Saleh, Ahmed Mahdi Muhammad (American Journal of Biodiversity, 2025)
This study investigates the effect of laser intensity on the morphology of porous silicon (PS), a material with extensive applications in optoelectronics, sensing, and biomedical fields. While previous research has explored PS formation and its photoluminescence properties, the influence of varying laser intensity during photoelectrochemical etching remains insufficiently addressed. Using an n-type silicon wafer, PS layers were fabricated under different laser illumination intensities (30–40 mW/cm²) in a hydrofluoric acid-based etching solution. Structural and morphological analyses were conducted using scanning electron microscopy (SEM) to assess porosity, pore shape, and layer thickness. The findings reveal a direct correlation between laser intensity and pore size, with higher intensities leading to increased pore widening and interconnectivity. These results highlight the potential for laser-controlled etching to optimize PS properties for targeted applications. The study contributes to advancing precision control in nanostructured silicon fabrication.